2023
DOI: 10.3390/nu15112505
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Neuronutrition in Prevention and Treatment of Neurological Disorders

Abstract: The term neuronutrition has been proposed as part of nutritional neuroscience, studying the effects of various dietary components on behavior and cognition. Other researchers underline that neuronutrition includes the use of various nutrients and diets to prevent and treat neurological disorders. The aim of this narrative review was to explore the current understanding of the term neuronutrition as the key concept for brain health, its potential molecular targets, and perspectives of its nutritional approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…Some studies suggested that adherence to a healthy diet pattern, such as a Mediterranean diet, is associated with a lower risk of cognitive impairment [ 23 , 24 ]. This is attributed to the presence of several neuro-nutritional components in the diet [ 25 ]. For example, the consumption of omega-3 fatty acids from fish and plant sources can enhance cognitive health and mental health [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that adherence to a healthy diet pattern, such as a Mediterranean diet, is associated with a lower risk of cognitive impairment [ 23 , 24 ]. This is attributed to the presence of several neuro-nutritional components in the diet [ 25 ]. For example, the consumption of omega-3 fatty acids from fish and plant sources can enhance cognitive health and mental health [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this brief narrative review is to explore the current literature and highlight potential of gender-specific dietary habits and their impact on neuroinflammatory states that may contribute to AD pathogenesis. Neuronutrition, in this regard, entails the study and exploration of nutrients, diet, eating behavior, and food environments and their interplay with epigenetic, immune, metabolic, and psychosocial constructs in the development of neurological disorders ( Badaeva et al, 2023 ). This review further aims to include the additional level of gender considerations in neuronutrition, which are important factors to consider in dietary advice during clinical encounters and dietary guidelines for the public.…”
Section: Introductionmentioning
confidence: 99%
“…The detrimental effects of disturbances in the gut-brain axis have also gained increasing recognition in the development and exacerbation of neurological and gastrointestinal disorders. The imbalance of intestinal microbiota can result from viral/bacterial infections, antibiotic use, and specific dietary regimens, and has been implicated in neuroinflammatory processes that are linked to the pathogenesis of illnesses such as PD and Alzheimer's Disease (AD) [5]. Conversely, neurological conditions such as PD, AD, multiple sclerosis, and chronic stress have been found to affect gut function and exacerbate inflammatory processes, including irritable bowel syndrome and leaky gut.…”
mentioning
confidence: 99%
“…Conversely, neurological conditions such as PD, AD, multiple sclerosis, and chronic stress have been found to affect gut function and exacerbate inflammatory processes, including irritable bowel syndrome and leaky gut. [5] In the study conducted by Valenzuela-Zamora (2022), the relationship between food selectivity (and especially the elimination of nutrient-dense foods that modulate gut microbiota) in children with Autism Spectrum Disorder (ASD) and the development of gastrointestinal disorders (GID) was explored [6]. GIDs such as constipation, diarrhea, abdominal pain, and growth delays are reported in approximately 80% of children with ASD, and it is believed to be a result of intestinal dybiosis which leads to the increase in inflammatory bacteria such as Enterobacteriaceae, Salmonella Escherichia/Shigella, and Clostridium XIVa.…”
mentioning
confidence: 99%
See 1 more Smart Citation